Psychosomatic symptoms, social support and self worth among the elderly in Hong Kong. Issue 4 (December 1988) - Ho, S C; Donnan, S P; Sham, A
Abstract : A prospective study to test the relationship between social support and health outcomes among the 1000 elderly Chinese subjects aged 70+ is being carried out in a Hong Kong New Town. This paper reports on the study factors related to psychosomatic complaints based on the first phase cross sectional data. Logistic regression analysis shows that being female, living in institutions, having a low level of social support and a low level of self worth independently increased the risk of developing a high level of psychosomatic symptoms. The relative risks for these factors range from 1.4 to 1.9 and all were significantly different from unity.